Kajian Efektivitas Kebijakan Fiskal pada Rumah Susun Sederhana Milik - Sabaruddin, Arief (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
The background of this study is about the increasing of investment finance of flat supply, but in the other hand people can't reach it anymore because of the sustaining of economical crisis. The number of unemployment is still high, and it makes some people hard to get a good neighborhood. The high number of new houses and backlog's need can't be facilitated completely yet by government. The effectively of subsidy is not seen yet, this study done to identify more the effective forms of fiscal subsidy which is done continually until now : which is most effective of tax and acceptance subsidy in the own flat supply. From the result of the study seen that an acceptance subsidy is more effective on increasing people's affordability than a tax subsidy one.